2020
DOI: 10.5014/ajot.2020.74s1-po2513
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Its Effects on Sophomore College Students’ Grade Point Averages

Abstract: Date Presented 03/26/20 This study examined the impact of smartphone addiction on freshman college student grade point averages (GPAs). A correlational analysis examined the GPAs of 65 college students and compared it to their self-reported Smartphone Addiction Inventory scores. While there appears to be an association between increased addiction and decreased GPA, these were not statistically significant. These findings can help explore smartphone addiction and its impact on academic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous researchers have identified problematic patterns and behaviors of smartphone use ( Kim, 2019 ; Samaha & Hawi, 2016 ), and there has been in-depth research on the variety of harms caused by CPA, such as family conflict ( Turel et al, 2008 ), decrease in sleep quality, and academic performance ( Lisewski et al, 2020 ; Zhang & Wu, 2020 ). Generally speaking, smartphones' accessibility and diverse internet-based functions make it even more addictive than other technology addictions ( Lin et al, 2016 ), and its properties during Covid-19 would be unique since it can help people escape reality and obtain pleasure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous researchers have identified problematic patterns and behaviors of smartphone use ( Kim, 2019 ; Samaha & Hawi, 2016 ), and there has been in-depth research on the variety of harms caused by CPA, such as family conflict ( Turel et al, 2008 ), decrease in sleep quality, and academic performance ( Lisewski et al, 2020 ; Zhang & Wu, 2020 ). Generally speaking, smartphones' accessibility and diverse internet-based functions make it even more addictive than other technology addictions ( Lin et al, 2016 ), and its properties during Covid-19 would be unique since it can help people escape reality and obtain pleasure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that in-class CPU and CPU at night were negatively related to the overall GPA of college students. Negative aspects included (attention-drawing) classroom notifications (Junco & Cotten, 2012 ; Kim et al, 2021 ), multitasking and task-switching (Alvarez-Risco et al, 2020 ; Uzun & Kilis, 2019 ), “fear of missing out” (Chen & Yan, 2016 ), lack of motivation or a sense of boredom (Hawi & Samaha, 2017 ), and cell phone addiction (Lisewski et al, 2020 ; De-Sola Gutiérrez et al, 2016 ). YA’s, encountered with negative aspects of CPU for academic performance, scored poorly in exams (Uzun & Kilis, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research explores the hypothesis that higher smartphone usage will result in increased addiction to the mobile phone and associated problems. In the past studies has found problematic pattern and behaviors of smartphone usage (Sohn et al, 2019), and there has been extensive research on the various harms produced by mobile phone addiction, including family conflict, decreased sleep quality and academic performance (Lisewski et al, 2020;Zhang & Wu, 2020). Generally, smartphone addiction is more addictive than other technology addiction.…”
Section: Literature Review Smartphone Addictionmentioning
confidence: 99%